2020
DOI: 10.3389/fphar.2020.573475
|View full text |Cite
|
Sign up to set email alerts
|

Propionic Acid Targets the TLR4/NF-κB Signaling Pathway and Inhibits LPS-Induced Intestinal Barrier Dysfunction: In Vitro and In Vivo Studies

Abstract: Intestinal barrier dysfunction contributes to the development of intestinal diseases. Propionic acid (PA), a metabolite generated by anaerobic fermentation of dietary fiber in the intestinal cavity, has been proved to exert anti-inflammatory effects in a variety of diseases. However, the exact role of PA in LPS-induced intestinal barrier dysfunction is still unclear. Accordingly, we examined the latent mechanism of PA and its protective role in LPS-induced intestinal barrier dysfunction by both in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…An increment in propionic acid levels, whose production in our study was strongly stimulated in the presence of IDW, has been previously reported after the intake of grape/wine polyphenols and the adherence to the Mediterranean diet [ 50 , 51 , 53 ]. Furthermore, a recent study has reported that this acid promoted cell migration, inhibited activation of NLRP3 inflammasome, and maintained intestinal barrier function in LPS-induced IEC-6 cells [ 54 ]. Besides, some species belonging to the Akkermansia genus, such as Akkermansia municiphila , considered acetate and propionate producing bacteria [ 55 ], have been reported to enhance the expression of TJ proteins in Caco-2 cells [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…An increment in propionic acid levels, whose production in our study was strongly stimulated in the presence of IDW, has been previously reported after the intake of grape/wine polyphenols and the adherence to the Mediterranean diet [ 50 , 51 , 53 ]. Furthermore, a recent study has reported that this acid promoted cell migration, inhibited activation of NLRP3 inflammasome, and maintained intestinal barrier function in LPS-induced IEC-6 cells [ 54 ]. Besides, some species belonging to the Akkermansia genus, such as Akkermansia municiphila , considered acetate and propionate producing bacteria [ 55 ], have been reported to enhance the expression of TJ proteins in Caco-2 cells [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…High-dose propionate has been reported to reduce LPS-induced inflammatory response in mouse endothelial cells and alveolar macrophages in a TLR-4 dependent manner ( 55 ). Another report showed the protective effect of PA against IκBα degradation and p65 translocation in LPS-treated IEC-6 cells ( 56 ), which suggests the suppression of the NF-κB/TLR-4 pathway by PA. In the present study, PA directly suppressed the HMGB-1 triggered TLR-4 activation in macrophages and suppressed TNF-α production.…”
Section: Discussionmentioning
confidence: 95%
“…TLR4 plays a key role in inherent immunity by activating proinflammatory pathways in different cell types and inducing cytokine generation. The TLR4/NF-κB signaling pathway has been considered a major modulator of the inflammatory response [23]. TLR4 signaling is required for the induction of NEC in both mice and patients [24].…”
Section: Discussionmentioning
confidence: 99%